A control architecture for continuous production processes based on industry 4.0: water supply systems application - Edgar Chacón; Luis Alberto Cruz Salazar; Juan Cardillo; Yenny Alexandra Paredes Astudillo (Journal of Intelligent Manufacturing, 2021)
Industry 4.0 (I4.0) brings together new disruptive technologies, increasing future factories' productivity. Indeed, the control of production processes is fast becoming a key driver for manufacturing operations. Manufacturing control systems have recently been developed for distributed or semi-heterarchical architectures, e.g., holonic systems improving global efficiency and manufacturing operations' reactiveness. So far, previous studies and applications have not dealt with continuous production processes, such as applications for Water Supply System (WSS), oil refining, or electric power plants. The complexity of continuous production is that a single fault can degrade extensively and even cause service disruption. Therefore, this paper proposes the Holonic Production Unit (HPU) architecture as a solution to control continuous production processes. An HPU is created as a holon unit depicting resources in a continuous process. This unit can detect events within the environment, evaluate several courses of action, and change the parameters aligned to a mission. The proposed approach was tested using a simulated model of WSS. The experiments described in this paper were conducted using a traditional WSS, where the communication and decision-making features allow the application of HPU. The results suggest that constructing a holarchy with different holons can fulfill I4.0 requirements for continuous production processes.
Keywords: 620; Continuous processes; Holonic manufacturing systems; HMS; Industry 4.0; Intelligent industrial automation; Water supply systems